Job satisfaction among Malaysian employees: an application of Spector’s Job Satisfaction Survey in the South East Asian Context - R Zirwatul Aida R Ibrahim,; Keis Ohtsuka,; Mazidah Mohd Dagang,; Azlina Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Job satisfaction explains individuals’ reactions towards their jobs. Many studies find that job satisfaction is a well-known construct that is widely used to study work-related well-being; and contributes significantly to employees’ overall quality of life. The current paper examines job satisfaction among Malaysian employees using the Job Satisfaction Survey (JSS). In particular, the present study compares the job satisfaction levels of Malaysian samples with those of a previously reported study involving samples from Singapore and the United States. Results of one sample t-test reveals statistically significant differences in pay, promotion, fringe benefits, contingent rewards, supervision, co-workers and nature of work subscales. No cultural influence exists between Malaysian and Singapore samples in terms of perceived operating conditions satisfaction. Similarly, no statistically significant difference exists between Malaysian and the United States perception towards the communication facet. Furthermore, the results of factor analysis support the previous study, suggesting possible cultural differences in the understanding of, and consensus regarding, the structure of the job satisfaction scale.